The effect of the Malaysian food guideline guidance on a group of overweight and obese women during Ramadan - Suriani, Ismail; Shamsuddin, Khadijah; Abdul Latif, Khalib; Abu Saad, Hazizi (Saudi Arabian Armed Forces Hospital, 2015)
Objectives: To determine the effect of imparting knowledge of the Malaysian Food Guideline (MFG) on a group of overweight and obese women during Ramadan.